The Influence of Medical Services and Work Motivation on Healthcare Workers' Performance Mediated By Job Satisfaction at RSU KMC Luragung - Huda, Cecep Saeful; Widjaja, Daniel (Syntax Corporation, 2026)
This study aims to analyze the effect of medical service incentives and work motivation on healthcare workers’ performance, with job satisfaction as a mediating variable at KMC Luragung General Hospital. A quantitative approach was applied using a survey method involving all 98 healthcare workers through saturated sampling. Data were collected using Likert-scale questionnaires and analyzed using Structural Equation Modeling (SEM) with SmartPLS. The results indicate that medical service incentives have a positive and significant effect on job satisfaction but a negative direct effect on healthcare workers’ performance. Work motivation has a positive and significant influence on both job satisfaction and performance. Job satisfaction is the most dominant factor affecting performance and significantly mediates the relationships between medical service incentives, work motivation, and performance. These findings suggest that improving healthcare workers’ performance requires not only financial incentives but also comprehensive efforts to enhance job satisfaction and motivation. This study is expected to provide useful insights for hospital management in developing sustainable performance improvement strategies.